Clinical neuropathology of early‐stage Pick's disease initially diagnosed as depressive disorder: A case report and case series comparison - Araki Kimura; Ito Kawakami; Kenji Ikeda; Akito Nagakura; Kazuhiro Niizato; Kenichi Oshima; Tadafumi Kato; Masato Hasegawa (PCN Reports, 2025)
Abstract Background Pick's disease (PiD) is a subtype of frontotemporal lobar degeneration. However, the pathogenesis and symptomatic lesions remain unclear. We report a case of PiD with a short disease duration and compare it to a case series to reveal the association between degenerative patterns and clinical manifestations. Case Presentation The patient showed a marked decline in motivation at the age of 54 years. He was admitted with a clinical diagnosis of depressive disorder at the age of 56 years. He exhibited only apathy and lacked typical behavioral symptoms. Specialist observation revealed behavioral symptoms such as disinhibition, a lack of empathy, and hyperorality that had previously unnoticed by the patient's family members. The patient died of acute heart failure 4 days after hospitalization. Postmortem examination revealed a brain weight of 1090 g, with focal atrophy of the bilateral frontal and temporal lobes. Neuropathological findings mainly presented as numerous Pick bodies (PBs), mainly in the frontal lobe and hippocampus. PBs were immunopositive for phosphorylated tau and 3‐repeat tau but negative for 4‐repeat tau. The pathological findings in this case corresponded to phase II of PiD staging as defined in a previous study. Conclusion The clinical symptoms in this case, primarily characterized by apathy with minimal behavioral symptoms, were consistent with the predominant pathological involvement of the dorsolateral frontal lobe. The present case was interpreted as early‐phase PiD. A comparison of the case series suggested that early‐phase PiD cases may help clarify the association between early clinical manifestations and focal degenerative lesions in the frontal lobe.